Quantitation of mycotoxins in food and feed from Burkina Faso and Mozambique using a modern LCMS/MS multitoxin method - Warth, B.; Parich, A.; Atehnkeng, J.; Bandyopadhyay, Ranajit; Schuhmacher, R.; Sulyok, M.; Krska, R. (American Chemical Society, 2012)
In this study an LC-MS/MS multitoxin method covering a total of 247 fungal and bacterial metabolites was applied to the analysis of different foods and feedstuffs from Burkina Faso and Mozambique. Overall, 63 metabolites were determined in 122 samples of mainly maize and groundnuts and a few samples of sorghum, millet, rice, wheat, soy, dried fruits, other processed foods and animal feeds. Aflatoxin B1 was observed more frequently in maize (Burkina Faso, 50% incidence, median = 23.6 μg/kg; Mozambique, 46% incidence, median = 69.9 μg/kg) than in groundnuts (Burkina Faso, 22% incidence, median = 10.5 μg/kg; Mozambique, 14% incidence, median = 3.4 μg/kg). Fumonisin B1 concentrations in maize were higher in Mozambique (92% incidence, median = 869 μg/kg) than in Burkina Faso (81% incidence, median = 269 μg/kg). In addition, ochratoxin A, zearalenone, deoxynivalenol, nivalenol, and other less reported mycotoxins such as citrinin, alternariol, cyclopiazonic acid, sterigmatocystin, moniliformin, beauvericin, and enniatins were detected. Up to 28 toxic fungal metabolites were quantitated in a single sample, emphasizing the great variety of mycotoxin coexposure. Most mycotoxins have not been reported before in either country.